(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1854)
In reference to an earlier article by Daniel Wilson regarding a bronze seal matrix, Professor Porter states that the Hebrew inscription on the matrix should be read as ’Solomon, son of Isaac Amamos: these are his tapestries’. He argues that this seal would have been used by either a manufacturer or a merchant to mark out his goods. He goes on to refute that there is a Jewish cultural aversion to portraying living beings in sculpture or engraving, either historically or in contemporary art. He discusses the basis of this misunderstanding and cites some examples of Jewish manuscripts that contain illustrations and engravings of people and animals. Professor Porter does not feel confident dating the seal matrix without historical record of its owner, but he does suggest that the item may be Spanish in origin.